2022
DOI: 10.3390/nu14204226
|View full text |Cite
|
Sign up to set email alerts
|

Added Sugar, Sugar-Sweetened Beverages, and Artificially Sweetened Beverages and Risk of Cardiovascular Disease: Findings from the Women’s Health Initiative and a Network Meta-Analysis of Prospective Studies

Abstract: Much remains unknown about the role of added sugar in relation to cardiovascular disease (CVD) and the relative contributions of sugar-sweetened beverages (SSB) or artificially sweetened beverages (ASB) to CVD risk. Among the 109,034 women who participated in Women’s Health Initiative, we assessed average intakes of added sugar, SSB and ASB, and conducted Cox regression to estimate the hazard ratios (HRs) and their 95% confidence intervals for CVD risk. The consistency of findings was compared to a network met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…33 Moreover, the sweeteners themselves may increase the production of free radicals and affect the balance between oxidant and antioxidant. 34,35 Consistently, our study found that there was a positive association of added sugars and preserves consumption with the risk of incident VTE. Tea Consumption and Venous Thromboembolism Xiang et al…”
Section: Discussionsupporting
confidence: 82%
“…33 Moreover, the sweeteners themselves may increase the production of free radicals and affect the balance between oxidant and antioxidant. 34,35 Consistently, our study found that there was a positive association of added sugars and preserves consumption with the risk of incident VTE. Tea Consumption and Venous Thromboembolism Xiang et al…”
Section: Discussionsupporting
confidence: 82%
“…26 Similarly, among 109 043 females in the WHS, during an average of 17.4 years of follow-up, 11 597 CVD events occurred. 27 Higher intake of added sugar (≥15.0% energy intake daily) was positively associated with total CVD (HR, 1.08 [95% CI, 1.01–1.15]). Consuming ≥1 servings of SSBs or ASBs daily was associated with 1.29 ([95% CI, 1.17–1.42]) and (1.14 [95% CI, 1.03–1.26]) higher risk of total CVD, respectively.…”
Section: Total Cardiovascular Diseasesmentioning
confidence: 99%
“…A meta-analysis [29 ▪ ] found an increased risk of coronary heart disease (CHD) (1.11; 1.04–1.08) and ischaemic stroke (1.10; 1.01–1.19), but the results on total CVD events (1.09; 0.96–1.24) were not significant. Similar findings from the Women's Health Initiative cohort and other PCS have shown that for every 1 serving/day increase of beverages that contain NAS, the risk of CHD increased by 35% (1.35; 1.16–1.57), the risk of ischaemic stroke increased by 30% (1.30; 1.10–1.53), and, unlike in the aforementioned meta-analysis, total CVD risk increased by 29% (1.29; 1.17–1.42) [30 ▪▪ ].…”
Section: Nutritive Artificial Sweetenersmentioning
confidence: 75%
“…Briefly, the evidence seems to show that a high consumption of both NAS and nNAS is associated with an increased CVD risk. The recent results published by Yang et al [30 ▪▪ ] on the Women's Health Initiative cohort found a 24% (1.24; 1.04–1.48) and 14% (1.14; 1.03–1.26) increase in ischaemic stroke and CVD risk associated with an intake of at least 1 serving/day of nNAS beverages, respectively. Nevertheless, as with obesity, nNAS may be an appropriate option for reducing NAS and sugar intake, thus mitigating their poor effects.…”
Section: Non-nutritive Artificial Sweetenersmentioning
confidence: 97%